The role of irregular eating behaviors in metabolic dysfunction-associated steatotic liver disease: evidence from a multicenter cross-sectional study in China - Xingxing Ren; Miao Zhang; Xiaoyang Sun; Lili Zheng; Yufang Bi; Qiang Li; Lirong Sun; Fusheng Di; Yushan Xu; Dalong Zhu; Yanyan Gao; Yuqian Bao; et al. (Journal of Translational Medicine)
Abstract Background Irregular eating patterns, such as skipping breakfast and late dinner consumption, have been linked to adverse metabolic profiles. However, the impact of these behaviors or their combined effect on metabolic dysfunction-associated steatotic liver disease (MASLD) remains unclear. Methods In this multicenter cross-sectional study, we analyzed data from 1965 adults recruited from diabetes, obesity, and metabolic disease clinics in six municipalities/provinces in China. Participants were categorized for analysis based on two irregular eating habits assessed by monthly frequency: skipping breakfast and late dinner consumption. For individual analyses, each habit was treated as a binary variable, dividing participants into two groups (e.g., skippers vs. non-skippers). For the combined analysis, these habits were aggregated to form a three-level ordinal variable, which classified participants based on the number of habits they reported: “No” (zero), “Medium” (one), or “Severe” (both). We employed logistic regression models to calculate the odds ratios (ORs) for MASLD associated with skipping breakfast, late dinner consumption, and their combination, after adjusting for key demographic, lifestyle, and metabolic factors. Results The prevalence of MASLD was higher among breakfast skippers compared to those who ate breakfast regularly (52.9% vs. 47.2%, p = 0.023), and similarly higher among late dinner eaters compared to those with regular dinner times (54.4% vs. 46.8%, p = 0.003). In the combined analysis, a graded relationship was observed across the three-level ordinal variable, with MASLD prevalence increasing from 46.5% in the “No” irregular eating group, to 50.3% in the “Medium” irregular eating group, and 55.5% in the “Severe” irregular eating group (p = 0.01). After multivariable adjustment, skipping breakfast, late dinner consumption, and the combination of these behaviors were each independently associated with higher odds of MASLD. This was highlighted by a clear dose–response relationship for the combined behaviors, where the odds of MASLD systematically increased with the severity of irregular eating (from “No” to “Medium” to “Severe”). Notably, the “Severe” irregular eating group, representing those with both habits, had a 65% higher odds of MASLD compared to those with none (OR = 1.65, 95% CI 1.17–2.34, p = 0.004). Conclusions Our study indicates that irregular eating behaviors, such as skipping breakfast and late dinner consumption, as well as their combination, are significantly associated with a higher prevalence of MASLD.